PENERAPAN BIMBINGAN KELOMPOK BELAJAR UNTUK MENINGKATKAN KEPERCAYAAN DIRI DAN PRESTASI BELAJAR - Febriyanti Mutia Ningsih1; Alexon (UNIB Press, 2022)
This study aims to: 1) Describe the implementation of appropriate group guidance to increase students' self-confidence in mathematics subjects in class XI IPS SMA N 5 Kerinci, 2) Describe the implementation of group guidance to improve student achievement in mathematics subjects in class XI IPS SMA N 5 Kerinci, and 3) Describe the effectiveness of the implementation of group guidance to increase students' Learning Achievement in the mathematics subject of class XI IPS SMA N 5 Kerinci. The subjects of this study were students of XI IPS SMA N 5 Kerinci. The research method uses classroom action research (Classroom Action Research) and quasi-experimental (Quasi Experiment). Data collection techniques used in the study were observation sheets and test methods. Analysis of the data used values ​​are: 1) analysis of student confidence, 2) analysis of pre-test and post-test, 3) analysis of t-test student achievement. Based on the research results obtained: 1) The implementation of group guidance can increase the self-confidence of students in class XI Social Sciences SMA Negeri 5 Kerinci which is carried out in 4 stages, 2) The application of group guidance can improve student achievement in class XI IPS SMA Negeri 5 Kerinci, and 3) The implementation of group guidance can effectively increase the confidence and learning achievement of class XI IPS students at SMA Negeri 5 Kerinci. This research is one of the reference materials for further research in terms of self-confidence and motivation for students in the field of group guidance services